Primary hyperhidrosis: Implications on symptoms, daily life, health and alcohol consumption when treated with botulinum toxin. Issue 8 (15th February 2016) - Shayesteh, Alexander; Boman, Jens; Janlert, Urban; Brulin, Christine; Nylander, Elisabet
Abstract: Primary hyperhidrosis affects approximately 3% of the population and reduces quality of life in affected persons. Few studies have investigated the symptoms of anxiety, depression and hazardous alcohol consumption among those with hyperhidrosis and the effect of treatment with botulinum toxin. The first aim of this study was to investigate the effect of primary hyperhidrosis on mental and physical health, and alcohol consumption. Our second aim was to study whether and how treatment with botulinum toxin changed these effects. One hundred and fourteen patients answered questionnaires regarding hyperhidrosis and symptoms, including hyperhidrosis disease severity scale (HDSS), visual analog scale (VAS) 10‐point scale for hyperhidrosis symptoms, hospital anxiety and depression scale (HADS), alcohol use disorder identification test (AUDIT) and short‐form health survey (SF‐36) before treatment with botulinum toxin and 2 weeks after. The age of onset of hyperhidrosis was on average 13.4 years and 48% described heredity for hyperhidrosis. Significant improvements were noted in patients with axillary and palmar hyperhidrosis regarding mean HDSS, VAS 10‐point scale, HADS, SF‐36 and sweat‐related health problems 2 weeks after treatment with botulinum toxin. Changes in mean AUDIT for all participants were not significant. Primary hyperhidrosis mainly impairs mental rather than physical aspects of life and also interferes with specific daily activities of the affected individuals. Despite this, our patients did not show signs of anxiety, depression or hazardous alcohol consumption. Treatment with botulinum toxin reduced sweat‐related problems and led to significant improvements in HDSS, VAS, HADS and SF‐36 in our patients.